Implementasi Strategi Pembelajaran Afektif yang Dilakukan Nabi Khidir Kepada Nabi Musa Serta Implikasinya pada Zaman Sekarang - Rossa Zetria Idallah; Rossi Zetria Idallah; Gusmaneli Gusmaneli (Lembag, 2024)
This article aims to describe (tell) the form of implementation of affective learning carried out by the Prophet Khidir for the Prophet Musa and its application today. This research uses library research methodology and is qualitative in nature, because the data collected uses textual analysis contained in books and journals related to models, approaches, methods and learning techniques. The results of this research are the first in this study to obtain an understanding of affective learning strategies. Both characteristics of affective learning strategies. The three models of affective learning strategies. Fourth difficulty in affective learning strategies. Fifth, the implications of the affective learning strategy carried out by the prophet Khidir to the prophet Musa. Sixth: Implementation of today's affective learning strategies.